'Social work of boundaries': emerging multiple social work fields in post-Soviet Eurasia - An, Sofiya (European journal of social work, 2017)
The restructuring of welfare provisions in post-Soviet Kazakhstan, a newly independent state in Central Asia, has been characterized by the shift from the Soviet welfare system dominated by the state to the welfare mix consisting of the state, the market, and the nonprofit, nongovernmental sector. One of the features of the post-Soviet welfare reconfiguration has been the development of social work as a new approach to welfare provision and an emerging professional field. This analysis draws upon key informant interviews conducted in Kazakhstan over the summer of 2012 and multiple relevant policy texts. This paper examines how the emerging fields of social work in post-Soviet Kazakhstan have been shaped by the shifting national and global policy contexts. More specifically, I identify two major fields of social work within the nongovernmental and the governmental sectors that are influenced by different institutional environments. First, domestic nongovernmental organizations have been increasingly involved in the provision of social services; and second, new or reformed governmental organizations have begun to introduce social services and social work. As a result, social work has emerged not as a coherent, homogenous field but as distinct, fragmentary fields.